Perancangan dan Simulasi Sistem Absensi Mahasiswa Berbasis Mikrokontroler RFID dan NodeMCU ESP8266 - Junindo Abdillah; Iswidodo Iswidodo; Zainal Arifin (Radial : Jurnal Ilmiah Sains dan Rekayasa, 2023)
The attendance system or attendance recording is a separate problem in terms of practicality, especially if the attendance process is still done manually. One of the technological advancements is the Radio Frequency Identification (RFID) system. The RFID system is widely used as a security system device. This tool is designed by combining microcontroller work with RFID technology in a system. Data in the form of a unique code from an RFID tag is used as student data. Apart from being used as a media attendance device, RFID is added to its function as an automatic classroom access open device so that when students take attendance, the classroom door lock opens too which makes it easier for students and the campus. And also this tool is combined with the ESP-32 CAM camera module which is modified so that it can read a QR code containing student data in the form of numbers, even though the code reading speed is not as fast as a scanner but it can still function the same this will make it even easier when students take attendance when you forget to bring your attendance card.